Main operating room deliveries for patients with high-risk cardiovascular disease. Issue 1 (14th February 2023) - Albright, Catherine M; Steiner, Jill; Sienas, Laura; Delgado, Carlos; Buber, Jonathan
Abstract : Background: High-risk cardiovascular disease (CVD) prevalence in pregnant patients is increasing. Management of this complex population is not well studied, and little guidance is available regarding labour and delivery planning for optimal outcomes. Objective: We aimed to describe the process for and outcomes of our centre's experience with the main operating room (OR) caesarean deliveries for patients with high-risk CVD, including procedural and postpartum considerations. Study design: We performed a retrospective evaluation of pregnant patients with high-risk CVD who delivered in the main OR at a large academic centre between January 2010 and March 2021. Patients were classified by CVD type: adult congenital heart disease, cardiac arrest, connective tissue disease with aortopathy, ischaemic cardiomyopathy, non-ischaemic cardiomyopathy or valve disease. We examined demographic, anaesthetic and procedure-related variables and in-hospital maternal and fetal outcomes. Multidisciplinary delivery planning was evaluated before and after formalising a cardio-obstetrics programme. Results: Of 25 deliveries, connective tissue disease (n=9, 36%) was the most common CVD type, followed by non-ischaemic cardiomyopathy (n=5, 20%). Scheduled deliveries that went as initially planned occurred for six patients (24%). Fourteen (56%) were unscheduled and urgent or emergent. Patients in modified WHO Class IV frequently underwent unscheduled, urgent deliveries (64%). Most deliveries were safely achieved with neuraxial regional anaesthesia (80%) and haemodynamic monitoring via arterial lines (88%). Postdelivery intensive care unit stays were common (n=18, 72%), but none required mechanical circulatory support. There were no in-hospital maternal or perinatal deaths; 60-day readmission rate was 16%. Some delivery planning was achieved for most patients (n=21, 84%); more planning was evident after establishing a cardio-obstetrics programme. Outcomes did not differ significantly by CVD group or delivery era. Conclusions: Our experience suggests that short-term outcomes of pregnant patients with high-risk CVD undergoing main OR delivery are favourable. Multidisciplinary planning may support the success of these complex cases.